Eksistensi â€˜Illat dalam Mengukuhkan Teks Hadis-hadis Ruâ€™yat al-HilÄl dan Fungsinya dalam Pengembangan Hukum Islam - Busyro, Busyro (Al-Ahkam, 2018)
á¸¤isÄb and ruâ€™yat always be warm conversations when there is an early determination of Ramadhan and Shawwal. At that time, there are always two camps of scholars in reacting, the scholars who hold on to á¸¥isÄb (calculating the calendar) on one side, and on the other hand hold to ruâ€™yat al-hilÄl (seeing the moon directly). This in turn often leads to time differences in setting the beginning of the month among Muslims. With the aim to unite the people in starting their worship, some scholars try to understand the texts of these traditions about ruâ€™yat al-hilÄl by trying to find the 'illat (reason) of the laws of hadiths about ruâ€™yat al-hilÄl. Their study of the 'illat law resulted in the conclusion that the ruâ€™yat al-hilÄl is only a suitable means for the people that time and may not suitable for Muslims in this modern era. Therefore Muslims must use other wasÄ«lah (means) which further guarantee the realization of the purpose of law, namely modern astroÂnomy. The conclusion of the law from the side of the discovery of â€˜illat seems to be less suited to the purpose of ta'lÄ«l al-aá¸¥kÄm, is to establish textual texts in addition to discovering the forms of development of the texts.